Tinospora crispa (L.) Hook. f. & Thomson: A Review of Its Ethnobotanical, Phytochemical, and Pharmacological Aspects - Ahmad, Waqas; Jantan, Ibrahim; Bukhari, Syed N. A. (Frontiers in Pharmacology, 2016)
Tinospora crispa (L.) Hook. f. & Thomson (Menispermaceae), found in the rainforests or mixed deciduous forests in Asia and Africa, is used in traditional medicines to treat numerous health conditions. This review summarizes the up-to-date reports about the ethnobotany, phytochemistry, pharmacological activities, toxicology and clinical trials of the plant. It also provides critical assessment about the present knowledge of the plant which could contribute towards improving its prospect as a source of lead molecules for drug discovery. The plant has been used traditionally in the treatment of jaundice, rheumatism, urinary disorders, fever, malaria, diabetes, internal inflammation, fracture, scabies, hypertension, reducing thirst, increasing appetite, cooling down the body temperature and maintaining good health. Phytochemical analyses of T. crispa revealed the presence of alkaloids, flavonoids and flavone glycosides, triterpenes, diterpenes and diterpene glycosides, cis clerodane-type furanoditerpenoids, lactones, sterols, lignans and nucleosides. Studies showed that the crude extracts and isolated compounds of T. crispa possessed a broad range of pharmacological activities such as anti-inflammatory, antioxidant, immunomodulatory, cytotoxic, antimalarial, cardioprotective and anti-diabetic activities. Most pharmacological studies were based on crude extracts of the plant and the bioactive compounds responsible for the bioactivities have not been well identified. Further investigations are required to transform the experience-based claims on the use of T. crispa in traditional medicine practices into evidence-based information. The plant extract used in pharmacological and biological studies should be qualitatively and quantitatively analyzed based on its biomarkers. There should be detail in vitro and in vivo studies on the mechanisms of action of the pure bioactive compounds and more elaborate toxicity study to ensure safety of the plant for human use. More clinical trials are encouraged to be carried out if there are sufficient preclinical and safety data.